2021
DOI: 10.1038/s41598-020-80194-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of ribosomal protein network architectures

Abstract: To perform an accurate protein synthesis, ribosomes accomplish complex tasks involving the long-range communication between its functional centres such as the peptidyl transfer centre, the tRNA bindings sites and the peptide exit tunnel. How information is transmitted between these sites remains one of the major challenges in current ribosome research. Many experimental studies have revealed that some r-proteins play essential roles in remote communication and the possible involvement of r-protein networks in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 79 publications
0
21
0
Order By: Relevance
“…A recent interdisciplinary study has shown how r-protein networks have evolved toward a growing complexity through the coevolution of the r-protein extensions and the increasing number of connexions [ 46 ]. This revealed that network expansion is produced by the collective (co)-evolution of r-proteins leading to an asymmetrical evolution of the two subunits.…”
Section: Ribosome Signalling and Primordial Molecular Brainsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent interdisciplinary study has shown how r-protein networks have evolved toward a growing complexity through the coevolution of the r-protein extensions and the increasing number of connexions [ 46 ]. This revealed that network expansion is produced by the collective (co)-evolution of r-proteins leading to an asymmetrical evolution of the two subunits.…”
Section: Ribosome Signalling and Primordial Molecular Brainsmentioning
confidence: 99%
“…On the other hand, new types of molecular networks have been recently discovered in the ribosomes [ 44 , 45 , 46 ]. These “neuron-like” ribosomal protein (r-protein) networks display new properties compared to other “classical” biological networks [ 47 ]: they form mostly permanent connections through long disordered filaments and phylogenetically conserved tiny interfaces that have been compared to “molecular synapses”.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional centers of ribosomes actively communicate to perform ribosomal functions. The communication among functional centers is optimized by the coevolution of a non-random RP network [89]. These RP graphs harbor specific neuron-like properties that led to the realization of RPs being instrumental in the process of information transfer across ribosomal complexes [90,91].…”
Section: Cold-triggered Reprogramming Indicates That Spatial Constraints Adjust the Ribosomal Proteomementioning
confidence: 99%
“…These proteins are colocalized in bacterial and archaeal ribosomes and have very similar structures, related by a circular permutation. Here we refer to them with their classical domain names bL33 and aL42 [90] for clarity, however we and others have proposed that they should share the name uL33 [88,91]. We probed whether TwinCons can detect the ancestral relationship within the composite alignment of bL33 and aL42.…”
Section: Twincons: Score That Detects Sequence Similarity Between Pairs Of Proteinsmentioning
confidence: 99%